2020
DOI: 10.3389/fonc.2020.587343
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Survival-Associated Alternative Splicing Signatures in Lung Squamous Cell Carcinoma

Abstract: Purpose: Alternative splicing (AS) is a post-transcriptional process that plays a significant role in enhancing the diversity of transcription and protein. Accumulating evidences have demonstrated that dysregulation of AS is associated with oncogenic processes. However, AS signature specifically in lung squamous cell carcinoma (LUSC) remains unknown. This study aimed to evaluate the prognostic values of AS events in LUSC patients. Methods: The RNA-seq data, AS events data and corresponding clinical information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 72 publications
(95 reference statements)
0
14
0
Order By: Relevance
“…In addition, in our current study, we constructed the risk signature using these altered genes in m6A and AS events to associate with NSCLC prognosis, and the AUC of the ROC curves showed the sensitivity and specificity of LUAD and LUSC, respectively, which are better than other recent studies (Zhao et al, 2020) (Liu et al, 2020). In these risk signatures, a previous study showed that S100A14 overexpression was able to promote LUAD cell migration and invasion (Ding et al, 2018).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…In addition, in our current study, we constructed the risk signature using these altered genes in m6A and AS events to associate with NSCLC prognosis, and the AUC of the ROC curves showed the sensitivity and specificity of LUAD and LUSC, respectively, which are better than other recent studies (Zhao et al, 2020) (Liu et al, 2020). In these risk signatures, a previous study showed that S100A14 overexpression was able to promote LUAD cell migration and invasion (Ding et al, 2018).…”
Section: Discussionmentioning
confidence: 64%
“…Indeed, AS events is an important mRNA modification process and produce a large number of mRNA and protein isoforms with different regulatory functions (Bonnal et al, 2020;Liu et al, 2020). The prognostic value of the AS events in NSCLC has well been documented, for example, Zhao et al (2020) built a predictive model of aberrant AS events and predicated NSCLC prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some formula based on alternative splicing signature have been applied to quantify genomic instability degree (20). Recent studies have focused on the AS network, leading to the construction of prognostic signature models based on comprehensive AS events which suitable levels of predictivity and efficiency for carcinoma prognosis (21)(22)(23). Whether genomic instability-related AS events could effectively predict prognosis of cholangiocarcinoma remains unclear.…”
Section: Discussionmentioning
confidence: 99%